Elemental distribution analysis of nanoparticles by atom probe tomography - LEE, JI YEONG; Yoon, Sujin; NAM, YUN SIK; Kim, Yanghee; Park, Gi Hoon; Jeong, Young Woo; Cha, Min Ju; Lee, Ye Ji; Kim, Hae-Ryoung; Yu, Byung Yong; Ahn, Jae Pyoung (PSA-24, 2024)
Atom probe tomography (APT) has many kinds of advantages like as three-dimensional atomical resolution, high sensitivity of 10 ppm. Accurate imaging and compositional analysis have also been the key driving technological factor for advances in semiconductor, Li ion battery, display, thermoelectric devices, and oxide semiconductors. APT has been developed to characterize nanoscale feasures of materials, which is a unique instrument for three-dimensional analysis with atomic resolution. We introduce the specimen preparation method for APT analysis of nanoparticles. We measured several kinds of nanoparticles such as Au nanoparticles, core-shell nanoparticles, ZnSe nanoparitlces, silver nanoparticles. Herein, we investigated highly sensitive colorimetric determination of chlorite ion based on selective etching of concave cubic gold naoparticles lie as figure 1.